Test of lepton flavor universality in semileptonic B+c meson decays in proton-proton collisions at √s=13 TeV - Hayrapetyan, A.; Tumasyan, A.; Adam, W.; Andrejkovic, J. W.; Bergauer, T.; Chatterjee, S.; Damanakis, K.; Dragicevic, M.; Hussain, P. S.; Jeitler, M.; Krammer, N.; Li, A.; et al. (AMER PHYSICAL SOC, 2025)
A measurement of the ratio of branching fractions R(J/psi) = B(B-c(+) -> J/psi tau(+)nu(tau))/B(B-c(+) -> J/psi mu(+)nu(mu)) in the J/psi -> mu(+)mu(-), tau(+) -> mu(+)nu(mu)(nu) over bar (tau) decay channel is presented. This measurement uses a sample of proton-proton collision data collected at a center-of-mass energy of 13 TeV by the CMS experiment in 2018, corresponding to an integrated luminosity of 59.7 fb(-1). The measured ratio, R(J/psi) = 0.17(-0.17)(+0.18) (stat)(+0.21)(-0.22) (syst)(+0.19)(-0.18) (theo) = 0.17 +/- 0.33, agrees with the value of 0.2582 +/- 0.0038 predicted by the standard model, which assumes lepton flavor universality. By testing lepton flavor universality, this measurement is a probe of new physics using B-c(+) mesons, which are currently only produced at the LHC.
Keywords: Astronomy & Astrophysics; Physics